(untitled) (International Journal of Studies in Nursing, 2018)
Background: Cardiac disease in pregnancy is a leading cause of maternal and neonatal morbidity and mortality. Effective management is based upon close fetal and maternal monitoring during pregnancy and labour. The aim of the present study was to evaluate maternity nurses’ performance regarding management of intrapartum woman with cardiac disease. Research design: A quasi-experimental design was utilized to fulfil the aim of the study. Sample: A convenient sample of a total 64 maternity nurses was included in the present study. Setting: The present study was conducted in Obstetrical and Gynecological Department at Benha University Hospital. Tools: Two tools were utilized for data collection. I-A structured interviewing questionnaire which include two parts; Part 1: Socio demographic characteristics. Part2: Assessment of nurses’ knowledge regarding cardiac disease during pregnancy and labour which includes Physiological changes of cardiovascular system during pregnancy. Causes and risk factors, etc. II-Maternity nurses’ practice observational checklistwhich focus on management of cardiac women during labor including four stages of labour and Nursing care for moderate and high risk cases immediately after labour. Results: Shows significant improvement in nurses’ knowledge 57.8% compared to 90.6% post intervention. Also, improvement is clear in satisfactory level of practice after intervention, in first stage for example was 32.8 % pre intervention compared to 87.5% post intervention. there were highly statistical significance differences between mean score of both knowledge and practice regarding management of intrapartum woman with cardiac diseases between the pre and post intervention phases (p<0.001).Conclusion: the study concluded that research hypotheses are supported and educational intervention had appositive effect on improvement nurses ’knowledge and practice and in turn their performance regarding management of intrapartum woman with cardiac diseases. Recommendation: Periodic educational program for nursing staff in Obstetrics and Gynecology Department regarding nursing care of cardiac patients.